Pengaruh Ajaran Tarekat QAdiriyah wa Naqsyabandiyah Terhadap Perilaku Sosial Masyrakat Dukuh Pilang Desa Tulung Kecamatan Sampung: The Influence of the Teachings of the Qadiriyah wa Naqsyabandiyah Order on the Social Behavior of the Dukuh Pilang Community of Tulung Village, Sampung District - Fathonah, Siti; Setyawan, Agus; Khafidhoh, Khafidhoh (Journal of Community Development and Disaster Management, 2023)
Do Along with the development of the times, many deviant human behaviors, with increasingly sophisticated technology, humans are easily influenced by the outside world so that negative impacts easily penetrate human souls, positive activities are needed so that they can influence the socio-spiritual community. This thesis reports the results of the research, with the formulation of the problem: (1) what are the teachings of the Qadiriyah wa Naqsyabandiyah Order related to the socio-spiritual community (2) What is the influence of the teachings of the Qadiriyah wa Naqsyabandiyah Order on the socio-spiritual behavior of the Dukuh Pilang community, Tulung Village, Sampung District, with the procedure data collection through observation techniques, interviews and documentation. Based on the results of data analysis, it is concluded that there are a lot of positive influences from the teachings of the Qadiriyah wa Naqsyabandiyah Order that are felt by the congregation, making it feel more calm and peaceful in carrying out their daily lives, establishing friendship and making better relationships among fellow people, spiritual emotional life is more organized , making the congregation to always behave well towards family and society. Seiring dengan perkembangan zaman banyak perilaku manusia yang menyimpang, dengan adanya tekhnologi yang semakin canggih manusia mudah terpengaruh oleh dunia luar sehingga dampak Negatif mudah merasuki jiwa-jiwa manusia, di perlukannya kegiatan-kegiatan yang positif agar dapat mempengaruhi sosial spiritual masyarakat. Dalam Penelitian ini ada tiga pembahasan (1) Apa saja ajaran Tarekat Qadiriyah wa Naqsyabandiyah yang berkaitan dengan sosial spiritual masyrakat (2) Bagaimana pengaruh ajaran Tarekat Qadiriyah wa Naqsyabandiyah terhadap perilaku sosial spiritual masyrakat Dukuh Pilang Desa Tulung Kecamatan Sampung, dengan prosedur pengumpulan data melalui teknik observasi,wawancara dan dokumentasi. Berdasarkan hasil analisis data di peroleh simpulan bahwa banyak sekali pengaruh positif ajaran Tarekat Qadiriyah wa Naqsyabandiyah yang di rasakan jamaah, menjadikan lebih terasa tenang dan damai dalam menjalankan kehidupan sehari-harinya, menjalin silahturahmi dan menjadikan hubungan lebih baik antar sesama masyrakat kehidupan emosional spiritual semakin tertata, menjadikan jamaah untuk senantiasa berperilaku baik terhadap keluarga dan masyrakat.